Integrasi Nilai-Nilai Konservasi dalam Pendidikan Formal dan Nonformal untuk Meningkatkan Literasi Ekologis dan Kesadaran Keberlanjutan Generasi Muda - Dewi Saraswati; Rahmayati Rahmayati; Islamul Hadi; Evy Aryanti (Pelantar Press, 2026)
This study explores the integration of conservation values in both formal and nonformal education and examines their roles in fostering ecological literacy and sustainability awareness among younger generations. Employing a qualitative descriptive design, the research is based on a systematic literature review of relevant scientific publications from the past decade. The findings reveal that formal education incorporates conservation values through curriculum development, institutional policies, innovative pedagogical strategies, and the use of digital technologies that support sustainability-oriented learning. Meanwhile, nonformal education enhances this integration through nature-based experiential learning, place-based approaches, active community participation, and youth involvement in collaborative environmental initiatives. This multi-pathway integration creates a comprehensive learning ecosystem that facilitates the internalization of ecological values across cognitive, affective, and behavioral dimensions. Furthermore, conservation education significantly contributes to improving environmental understanding, nurturing pro-environmental character, and strengthening youth engagement in sustainable practices. In conclusion, conservation education holds a strategic role in advancing inclusive and quality education, as highlighted in Goal 4 of the Sustainable Development Goals